2017
DOI: 10.1016/j.jjcc.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of spontaneous coronary artery dissection treated by percutaneous coronary intervention with optical coherence tomography

Abstract: The clinical outcomes of OCT-guided PCI for SCAD were favorable, as well as those for other ACS etiologies. OCT-guided PCI could become a therapeutic option for SCAD compromised with ongoing necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Coronary heart disease is a kind of heart disease caused by atherosclerotic changes in coronary arteries, narrowing or obstruction of vascular lumen, and hypoxia and ischemic necrosis of myocardial cells (Nishiguchi et al, 2017). It covers a wide range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary heart disease is a kind of heart disease caused by atherosclerotic changes in coronary arteries, narrowing or obstruction of vascular lumen, and hypoxia and ischemic necrosis of myocardial cells (Nishiguchi et al, 2017). It covers a wide range.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that the application of AI deep learning techniques could effectively prevent the complications of coronary heart disease, improve the quality of clinical nursing and increase patient satisfaction. It is pointed out in some literatures that the high-risk patients with coronary heart disease show old age, long duration, medical history, disease characteristics such as lack of cognition and unhealthy life-style, therefore, the comprehensive collection of patients' data for feature screening will predict the risk of related complications in a more accurate way, providing a clear direction for the formulation of nursing plan and implementation of nursing (Kinnaird et al, 2018). In the observation group, AI deep learning techniques were applied to predict the possible complications of coronary heart disease in 14 patients, with an accuracy rate of 87.50%.…”
Section: Comparison Of Nursing Satisfaction Between the Two Groupsmentioning
confidence: 99%
“…Studies from coronary intervention have demonstrated that OCT not only helps to diagnose coronary dissection, but can also guide endovascular treatment ( 19 , 20 ). Stenting, as a salvage strategy, has been used to rescue patients with coronary dissection ( 21 ). Nevertheless, angiography-guided stenting of coronary dissection is often difficulty and carries additional risks.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-guided PCI for SCAD has shown favorable results, as well as those for other ACS etiologies. OCT-guided PCI could be considered a useful therapeutic option for the management of SCAD [10].…”
Section: Discussionmentioning
confidence: 99%